Relationship of Investment Motivation, Investment Knowledge and Minimum Capital to Investment Interest - Maharani, Amalina; Farhan Saputra (Journal of Law, Politic and Humanities, 2021)
The Literature Review article on the Relationship of Investment Motivation, Investment Knowledge, and Minimum Capital to Investment Interest is a scientific article that aims to build a research hypothesis on the influence between variables that it will use in further research within the scope of Financial Management. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley, and other academic online media. This Literature Review article results are 1) Investment Motivation is related to Investment Interest; 2) Investment Knowledge related to Investment Interest, and 3) Minimum Capital related to Investment Interest. Apart from these three exogenous variables that affect the endogenous variable of Investment Interest, there are still many other factors, including Income Expectation, Risk Perception, and Financial Literacy variables.